Enciclopedismul lui B.P. Hasdeu și specializarea contemporană - PILCHIN, Maria (BIBLIOPOLIS, 2026)
The term “encyclopedism” reflects, chronologically, the 18th-century philosophical movement, as well as the multilateral scholarship of human knowledge throughout history. In the context of the evolution of printing and the accumulation of scientific heritage, encyclopedism played a fundamental role in the progress of the book civilization, contributing to the creation of libraries, museums, and dictionaries that organized and systematized the epistemological universe of ideas. In contrast to specialization, encyclopedism promotes a generalizing approach to the process of wisdom. These two concepts are not antagonistic but rather complement each other. The article explores, as a case study, the encyclopedic activity of B.P. Hasdeu, highlighting that for him, encyclopedism was not an inoperative concept, but a necessity for organizing and systematizing knowledge, aimed at both elites and the general public. In the information age and the attention economy, encyclopedic ideas remain relevant, promoting collaboration and the development of a framework for global and continuous education. The article emphasizes that, although the paradigm of the universal encyclopedist is no longer in vogue, Hasdeu’s encyclopedic spirit can inspire adaptations of this concept in the context of current challenges such as the crisis of knowledge, illiteracy, anti-intellectual attitudes, etc.